Unquiet : a novel - Ullmann, Linn, 1966- (W.W. Norton & Company, 2019)
He is a renowned Swedish filmmaker and has a plan for everything. She is his daughter, the youngest of nine children. Every summer, since she was a little girl, she visits him at his beloved stony house surrounded by woods, poppies, and the Baltic sea. Now that she<U+2019>s grown up and he<U+2019>s in his late eighties, he envisions a book about old age. He worries that he<U+2019>s losing his language, his memory, his mind. Growing old is hard work, he says. They will write it together. She will ask the questions. He will answer them. When she finally comes to the island, bringing her tape recorder with her, old age has caught up with him in ways neither could have foreseen. Unquiet follows the narrator as she unearths these taped conversations seven years later. Swept into memory, she reimagines the story of a father, a mother, and a girl<U+2015>a child who can<U+2019>t wait to grow up and parents who would rather be children. A heartbreaking and darkly funny depiction of the intricacies of family, Unquiet is an elegy of memory and loss, identity and art, growing up and growing old. Linn Ullmann nimbly blends memoir and fiction in her most inventive novel yet, weaving a luminous meditation on language, mourning, and the many narratives that make up a life.